Konseling Behavioral dengan Teknik Modeling Melalui Lesson Study untuk Meningkatkan Kemandirian - Anggraini, Herna; Dantes, Nyoman; Dharsana, I Ketut (Jurnal Jurusan Bimbingan Konseling Undiksha, 2018)
This research was carried out aimed to determine the extent of the effectiveness of the implementation of behavioral counseling theory with modeling techniques to increase student independence and differences in the independence of students who were given behavioral counseling with modeling techniques and those that were not given to VII grade students of SMP Lab. Undiksha Singaraja. The sample of this study was determined using random sampling techniques, the data collection method in this study used the interview method, a diary, and the questionnaire independence Likert scale pattern. The method of analyzing the hypothesis test data uses t test. The results of this study indicate that there is the effectiveness of behavioral counseling modeling techniques for the independence of Grade VII students of SMP Lab. UNDIKSHA and there are differences in independence given behavioral counseling modeling techniques with those not given.Keywords: Behavioral Counseling, modeling technique, independence